Pathogenicity Assessment and Vaccine Efficacy of Fowl Adenovirus Serotype 4 and 11 Responsible for Inclusion Body Hepatitis Hydropericardium Syndrome in Broilers - Joshi, Kuldip V.; Dave, Chandrakant J.; Joddha, Harshrajsinh B.; Bhanderi, Bharat B.; Ghodasara, Dinesh J.; Kabariya, Digjay V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Thisstudy aimed to assess the pathogenicity and vaccine efficacy of fowl adenovirus serotypes 4 and 11, causing inclusion body hepatitis  hydropericardium syndrome in broilers. The study was carried out on 144-day-old Cobb broiler chicks divided into six experimental  groups, each of 24 birds. Group, I birds served as a control without any vaccine or viral challenge, while birds of Group II were  vaccinated with commercial vaccine on 6th day. Group III and IV birds were non-vaccinated and challenged with 107 TCID50 of FAdV  serotype 4 and 11, respectively, on the 27th day. In contrast, Group V and VI birds were vaccinated on the 6th day and challenged with  107 TCID50 of FAdV serotype 4 and 11 on the 27th day. The challenge of FAdV serotype 4 led to 66.66% mortality, and serotype 11  produced 5.00% mortality in the experimental groups. The challenge of the virus led to the production of clinical signs such as  depression, huddling, reduced feed intake, reluctance to move, and terminal gasping before death. Characteristic gross lesions of  IBH-HPS were observed in birds that died after the challenge of serotypes 4 and 11 of FAdV. The liver was enlarged with focal  areas of necrosis, subcapsular hemorrhages, and mild fatty changes. The heart was flabby, congested, and showed  hydropericardium with an accumulation of clear watery to a yellow jelly-like fluid in the pericardial sac. The kidneys were enlarged  and hemorrhagic. On microscopic examination, the liver showed multifocal areas of necrosis with infiltration of mononuclear cells,  mild fatty changes and large basophilic intranuclear inclusion bodies. The birds that died after the challenge of the virus were positive  for the presence of FAdV upon PCR. The vaccine efficacy study indicated that the vaccine provided satisfactory protection against Fowl  Adenovirus challenge in experimental groups V and VI.
Keywords: Fowl adenovirus; Inclusion Body Hepatitis; Poultry; Vaccine efficacy